TASKSAND OPPORTUNITIES OF FASHION EDUCATION IN COUNTRIES WITH TRANSITION ECONOMIES - Khurana, Karan; Riabchykov, Mykola (Problems of Engineer-Pedagogical Education, 2018)
Contradictions that exist between the demands of society, economy and culture and the actual state education in countries with transition economy, the possibility of fairly rapid restructuring of education in fashion design and insufficient development of the main approaches to educational content in the field, a wide range of tasks that are solved during the activity towards fashion design and insufficient attention to education in this areaare formulated. Aim of article is to prove the possibility of rapid restructuring of educational content in countries with economies in transition using the basic demands of society, economy and culture taking into account spectrum of problems solved in the activity towards fashion design. The paper formulate the basic problems of education, highlight their cause and justify the possibility of a quick resolution of fashion in reforming education. The basic provisions and competences to prepare master of fashion design on the basis of competence approach proposed by European project tuning are confirmed. The approaches to learning designers based on active learning methods, including the Socratic method are grounded. The methods of practical implementation of the performance diploma project are proposed. The result of the proposed method is the curriculum for master's degree in fashion design, which in its conceptual framework focuses on innovative technologies in education and design. This approach will accelerate the transformation of how design education and education in general, u will ultimately lead to increased learning.